A Geospatial Evaluation of 9-1-1 Ambulance Transports for Children and Emergency Department Pediatric Readiness. (17th February 2023) - Newgard, Craig D.; Malveau, Susan; Mann, N. Clay; Hansen, Matthew; Lang, Benjamin; Lin, Amber; Carr, Brendan G.; Berry, Cherisse; Buchwalder, Kyle; Lerner, E. Brooke; Hewes, Hilary A.; Kusin, Shana; et al.
Abstract: Objective: Whether ambulance transport patterns are optimized to match children to high-readiness emergency departments (EDs) and the resulting effect on survival are unknown. We quantified the number of children transported by 9-1-1 emergency medical services (EMS) to high-readiness EDs, additional children within 30 minutes of a high-readiness ED, and the estimated effect on survival. Methods: This was a cross-sectional study using data from the National EMS Information System for 5, 461 EMS agencies in 28 states from 1/1/2012 through 12/31/2019, matched to the 2013 National Pediatric Readiness Project assessment of ED pediatric readiness. We performed a geospatial analysis of children 0 to 17 years requiring 9-1-1 EMS transport to acute care hospitals, including day-, time-, and traffic-adjusted estimates for driving times to all EDs within 30 minutes of the scene. We categorized receiving hospitals by quartile of ED pediatric readiness using the weighted Pediatric Readiness Score (wPRS, range 0-100) and defined a high-risk subgroup of children as a proxy for admission. We used published estimates for the survival benefit of high readiness EDs to estimate the number of lives saved. Results: There were 808, 536 children transported by EMS, of whom 253, 541 (31.4%) were high-risk. Among the 2, 261 receiving hospitals, the median wPRS was 70 (IQR 57-85, range 26-100) and the median number of receiving hospitals within 30 minutes was 4 per child (IQR 2-11, range 1 to 53). Among all children, 411, 685 (50.9%) were taken to EDs in the highest quartile of pediatric readiness, and 180, 547 (22.3%) children transported to lower readiness EDs were within 30 minutes of a high readiness ED. Findings were similar among high-risk children. Based on high-risk children, we estimated that 3, 050 pediatric lives were saved by transport to high-readiness EDs and an additional 1, 719 lives could have been saved by shifting transports to high readiness EDs within 30 minutes. Conclusions: Approximately half of children transported by EMS were taken to high-readiness EDs and an additional one quarter could have been transported to such an ED, with measurable effect on survival.